Evaluation of Cholesterol as a Biomarker for Suicidality in a Veteran Sample. Issue 4 (21st April 2017) - Reuter, Chuck; Caldwell, Barbara; Basehore, Heather
Abstract: A reduction in total cholesterol may alter the microviscosity of the brain‐cell‐membrane, reducing serotonin receptor exposure. The resulting imbalance between serotonin and dopamine may lead to an increased risk for suicidality. The objective of this research was to evaluate total cholesterol as a biological marker for suicidality in a sample of US military veterans. The study population consisted of veterans who received care at the Coatesville Veterans Affairs Medical Center (VAMC) and were included in the Suicide Prevention Coordinator's database for having suicidal ideation with evidence of escalating intent, a documented suicide attempt, or committed suicide between 2009 and 2015. The veterans' medical data were obtained from the facility's computerized patient record system. The final sample was 188 observations from 128 unique veterans. Veterans with total cholesterol levels below 168 mg/dl appeared to have a higher suicide risk than those with higher levels. The cholesterol levels of veterans reporting suicidal ideation or attempt were significantly lower than the group reporting neither [ F (2, 185) = 30.19, p < .001]. When data from multiple visits were available, veterans reporting suicidal ideation or attempt had experienced a significant (20%) decrease in cholesterol levels from an earlier visit in which they did not report suicidality. A latent class analysis revealed that among other differences, suicidal veterans were younger, leaner, and had more anxiety, sleep problems, and higher education than those being seen for an issue unrelated to suicidality. © 2017 Wiley Periodicals, Inc.